The influence of the type of consumer packaging on the quality of cottage cheese during the shelf life - M. N. Shkolnikova; E. D. Rozhnov; M. S. Esipova (Современная наука и инновации, 2024)
The article summarizes information on the use of polymer materials and paper for consumer packaging of cottage cheese, as well as on the examination of consumer properties of cottage cheese sold in consumer markets of cities of the Russian Federation. Experimental data on the effect of the type of consumer packaging of cottage cheese on its quality and safety during the shelf life are presented. The degree of influence of the packaging material – parchment, laminated foil and a container made of polyvinyl chloride on the safety of cottage cheese with a fat content of 5% is shown.